Effectiveness of a psychosocial skills and characteristics development programme embedded into an English male professional soccer academy - Barraclough, J.; Grecic, D.; Harper, D.; Mitchell, T. (BASES Conference 2024, 2024)
Psychosocial skills and characteristics (PSCs) are believed to be the key drivers in realising development of potential in soccer academies (Till and Baker, 2020, Frontiers in Psychology 11, 1664-1078). The aim of this study was to explore the effectiveness of an individualised 21-week PSC development program in a male Category 3 soccer academy based on previous research (Mitchell, Cowburn, Piggott, Littlewood, Cook, and Till, 2022, Sport Psychologist, 36(2), 1-42; Mitchell, Cowburn, Alder, Till, Littlewood, Cook, and Piggott, 2024, International Sport Coaching Journal, (Ahead of Print), 1-13). Ethical approval was granted from the University of Central Lancashire`s institutional ethics committee (BAHSS2 0305). Nine players (age 12.63 ± 0.18 years) from the U13 squad volunteered to participate in the study. An action research methodology was used (Lewin, 1946, Journal of Social Issues 2, 34-46) whereby the lead researcher was embedded within the academy to plan, implement, and review the PSC development programme in accordance with academy coaches (n = 2). Data were gathered pre- and post PSC intervention using the psychological characteristics of developing excellence questionnaire version 2 (PCDEQ2) (Hill, MacNamara and Collins, 2019, European Journal of Sport Science, 19(4), 517-528) and performance profiles (Butler and Hardy, 1992, The Sport Psychologist, 6, 253-264). Changes in player PSCs were analysed using paired samples t-tests with Cohen`s d effect size used to determine the magnitude of change. For PCDEQ2 scores, small positive effects were noted for self-directed control and management (d = 0.31) and active coping (d = 0.27). Imagery and active preparation (d = -0.42), perfectionistic tendencies (d = -0.43) and seeking and using social support (d = -0.22) showed negative small effects. For the performance profile scores, moderate positive effects were observed on emotional control (d = 0.76), self-awareness (d = 0.52), and being a good learner (d = 0.47). Moderate negative effects were observed for commitment (d = -0.56), and concen tration (d = -0.79). In conclusion, a 21-week PSC development programme embedded within a Category 3 soccer academy had both small-to-moderate positive and negative effects on player PSCs. Further research is needed to explore effectiveness of approaches for delivering PSCs in soccer academy environ ments in conjunction with academy coaches.